2016
DOI: 10.1038/srep29844
|View full text |Cite|
|
Sign up to set email alerts
|

IL-33 Contributes to Schistosoma japonicum-induced Hepatic Pathology through Induction of M2 Macrophages

Abstract: Interleukin (IL)-33 is involved in T helper (Th)2-biased immune responses in mice infected with Schistosoma, but the precise mechanism remains to be elucidated. Herein, we investigated the role of IL-33 and its receptor ST2L in hepatic granuloma pathology induced by Schistosoma japonicum infection. We found that IL-33 induced the increased production of IL-5 and IL-13 from splenocytes and liver mononuclear cells (MNCs) of infected mice. The infected mice developed significantly higher number of ST2L-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 28 publications
(46 reference statements)
2
60
2
1
Order By: Relevance
“…It is known that IL-33 induces M2 polarization of macrophages (26,(28)(29)(30) and that M2 are essential for the excretion of schistosome eggs across intestinal tissues (14). It has also been reported that due to the impairment of their expulsion across the intestinal wall, more schistosome eggs accumulate in intestinal tissues (31,32).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is known that IL-33 induces M2 polarization of macrophages (26,(28)(29)(30) and that M2 are essential for the excretion of schistosome eggs across intestinal tissues (14). It has also been reported that due to the impairment of their expulsion across the intestinal wall, more schistosome eggs accumulate in intestinal tissues (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…1e), indicating that IL-33 may be dispensable for the excretion of schistosome eggs. Because several studies reported a pathogenic role for IL-33 in egg-induced liver pathology by an increased number of liver tissue eggs (25,26), we sought to see whether IL-33 de ciency would be associated with a decreased number of eggs in liver tissues of IL-33 −/− compared to WT mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations